Faktor yang Mempengaruhi Partisipasi Lansia dalam Kegiatan Perekonomian - Darmiati, Darmiati; Akbar K., Fredy; Hasrina, Hasrina (Mando Care Jurnal, 2021)
Every human will certainly experience what is called old age. Throughout the world the elderly (aged 60) grow rapidly and even faster than other age groups. In this case health and age factors are also one that results in a shortage of the elderly in meeting their needs, since the age factor in general is a state of psychological decline and physical decline. This is in contrast with the elderly who are also required to meet the needs of daily life. Economic problems make up a vital discussion among communities especially in the elderly, a multitude of factors, both that should allow the elderly to take part in increasing their own economy or, in turn, that must the elderly to sit at home quietly because of problems between health and other conditions. We have therefore decided to pursue research to see how the economic development of older people understudy the variables which give to economic liberalization. The research method we use on this study is a quantitative study method with sample withdrawal techniques conducted on a chance in which each sample is entitled to be asked a questionnaire, the results from the questionnaires we get are then analyzed and from the overall result it states that the number of liability is the dominant factor of the four variables of old leaders who take part in their economies.